2018
DOI: 10.14814/phy2.13911
|View full text |Cite
|
Sign up to set email alerts
|

Evidence in hypertensive rats of hypotensive effect after mandibular extension

Abstract: Previous studies in anesthetized normotensive rats demonstrated that a single mouth opening for 10 min obtained by an ad hoc dilator (mandibular extension [ME]) produced a blood pressure reduction by about 20 mmHg lasting for about 2 h and that once‐repeated ME prolonged this effect. We here describe these effects in hypertensive rats. Mean (intra) arterial blood pressure (MABP) and heart rate (HR) was followed for up to a maximum of 470 min after single or repeated 10 min‐lasting ME in two groups of anestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Our results confirm previous observations in SHR [17,18] showing a marked decrease in MBP and HR induced after two MEs and suggest, for the first time, a possible involvement of deiodinases in the compensative response to a hypotensive stimulus (ME) in rat brain cortex. So far, data available on deiodinases expression in the rodent brain are limited to observations in hyper-or hypo-thyroid conditions or in association with the brain maturation [15,26,27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results confirm previous observations in SHR [17,18] showing a marked decrease in MBP and HR induced after two MEs and suggest, for the first time, a possible involvement of deiodinases in the compensative response to a hypotensive stimulus (ME) in rat brain cortex. So far, data available on deiodinases expression in the rodent brain are limited to observations in hyper-or hypo-thyroid conditions or in association with the brain maturation [15,26,27].…”
Section: Discussionsupporting
confidence: 92%
“…Rats underwent a double mandibular extension (ME) treatment, in order to induce a hypotensive response throughout the trigeminal nerve stimulation [17,18]. In general, the facial area presents many autonomic reflexes having trigeminal fibers as afferent branches.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiment with double ME, ME2 caused a marked reduction of MABP (about 30 mmHg) lasting for the whole observation period (about 4 h), and a slight decrease of HR. These data are reported in Del Seppia et al (2018).…”
Section: Resultsmentioning
confidence: 67%
“…Recently, we have observed that ME is followed by a prolonged decline in mean blood pressure also in rats in which hypertension was induced by dexamethasone administration (20 µg/kg/day, subcutaneously for 7 days) and in spontaneously hypertensive rats (SHR). In both cases, the treatment induced a marked reduction in mean arterial blood pressure, which was much greater compared to that observed in normotensive rats [11].…”
Section: Introductionmentioning
confidence: 61%